Pengembangan Sistem Embedded Berbasis ARM CORTEX M7 untuk Pengukuran Frekuensi Sensor QCM Portable - Hudha, Lalu Sahrul; Santosa, Didik Rahadi; Sakti, Setyawan Purnomo (Majalah Ilmiah Teknologi Elektro, 2017)
In general, measurement using QCM sensor consists of oscillator, frequency counter, power supply, computer dan monitor. The result of measurement using QCM is usually presented in graph of frequency and time that calls sensogram. In order to make the measurement system more practical, there is a need to develope an embedded system. We developed a portable system which consist of a 32-bit microcontroller, frequency counter, display and data storage. The core microcontroller for the portable system is the ARM-Cortex-M7. The developed embedded system ables to measure the frequency of the sensor, displayed the data and simultaneously store the recorded data in a microSD. These functions are developed inside STM32F746NG by using Real Time Operating System. The freeRTOS was selected as the operating system.